Shifting discourses from boy preference to boy crisis: educating boys and nation building in neoliberal China. Issue 3 (4th May 2019) - Lin, Xiaodong; Mac an Ghaill, Mairtin
ABSTRACT: It is well established that China has emerged as a major economic power, resulting from the nation's neoliberal modernization. What is less understood is the socio-cultural and educational impact of this change on public institutions. This article focuses on the education system, which is currently seen as central to delivering the nation's modernization project, particularly through suzhi jiaoyu (education for quality). More specifically, we engage with a pervasive public discourse of a boy crisis. We suggest the need critically to explore the local (national) meanings within a contemporary Chinese context of this assumed projected crisis that appears to be established as a western phenomenon. We argue that the discourse of a boy crisis can be read as a strategic move to re-inscribe an earlier discourse, that of the boy preference, that in turn is discursively linked to nation building at a time of globally inflected socio-economic transformations.